The identification of archaeological eggshell using peptide markers. Issue 1 (1st January 2017) - Presslee, Samantha; Wilson, Julie; Woolley, Jos; Best, Julia; Russell, Douglas; Radini, Anita; Fischer, Roman; Kessler, Benedikt; Boano, Rosa; Collins, Matthew; Demarchi, Beatrice
ABSTRACT: Avian eggshell survives well in alkaline and neutral soils, but its potential as an archaeological resource remains largely unexplored, mainly due to difficulties in its identification. Here we exploit the release of novel bird genomes and, for the first time on eggshell, use MALDI-ToF (matrix-assisted laser desorption ionisation-time of flight) mass spectrometry in combination with peptide sequencing by LC-MS/MS. The eggshell proteome is revealed as unexpectedly complex, with 5755 proteins identified for a reference collection comprising 23 bird species. We determined 782 m/z markers useful for eggshell identification, 583 of which could be assigned to known eggshell peptide sequences. These were used to identify eggshell fragments recovered from a medieval site at Freeschool Lane, Leicester. We discuss the specificity of the peptide markers and highlight the importance of assessing the level of taxonomic identification achievable for archaeological interpretation.